Immigrant Entrepreneurship and Rural Tourism in a Left-Behind Region, Sayago (Zamora, Spain) - Rodríguez Rodríguez, Mercedes Ángeles; Mendoza, Cristóbal; Domínguez-Mujica, Josefina (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2026)
Rural Sayago (Zamora, Spain), on the Portuguese border, exemplifies long-term depopulation and ageing processes in Southern Europe. This study examines the tourism-migration nexus, asking how tourism development influences the arrival, settlement and economic incorporation of internal and international immigrants. We combine qualitative fieldwork from two projects—semi-structured interviews with migrant entrepreneurs in accommodation, hospitality and agritourism—with analysis of official demographic data. Results show that tourism-related activities enable livelihood diversification and self-employment that support newcomer settlement, especially internal in-migrants with inherited property and lifestyle international immigrants. Newcomers act as innovators, expanding rural accommodation and experience-based offers. However, seasonality, thin markets and limited services constrain broader demographic recovery. We conclude that rural tourism can stabilise population locally by enabling immigrant settlement, but it requires place-based policies that strengthen everyday infrastructures and trans-border coordination.